1988
DOI: 10.1177/000456328802500505
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Analysis of 6-Mercaptopurine and Metabolites in Extracellular Body Fluids

Abstract: A convenient HPLC assay, which allows for the simultaneous measurement in extracellular fluids of 6-mercaptopurine and four of its metabolites, 6-thioguanine, 6-mercaptopurine riboside, 6-thioxanthine and 6-thiouric acid is described. Solid phase extraction allows for the clean isolation of analytes from plasma, urine or cerebrospinal fluid. The simultaneous determination of 6-mercaptopurine and some of its major metabolites in extracellular fluids may contribute to the monitoring of patient compliance, bioava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A few methods for determination of both or one or the other compounds in human urine by HPLC with UV detection were described [106][107][108][109]. Almost all methods [106][107][108] make use of natural structural properties of thiopurines, which possess a well-defined absorption maximum in the ultraviolet spectrum. Recently, Zakrzewski [110] reported a post-column reaction detection method for HPLC determination of thioguanine, based on the sensitizing induction of thioguanine on iodine-azide reaction.…”
Section: Thiopurinesmentioning
confidence: 99%
“…A few methods for determination of both or one or the other compounds in human urine by HPLC with UV detection were described [106][107][108][109]. Almost all methods [106][107][108] make use of natural structural properties of thiopurines, which possess a well-defined absorption maximum in the ultraviolet spectrum. Recently, Zakrzewski [110] reported a post-column reaction detection method for HPLC determination of thioguanine, based on the sensitizing induction of thioguanine on iodine-azide reaction.…”
Section: Thiopurinesmentioning
confidence: 99%
“…The ideal method should allow the assessment of patient compliance with the treatment, together with measurement of the absorption, transport and accumulation of the cytotoxic metabolites (31). Studies concerning the quantification of 6-MP and its metabolites in the urine of patients showed that the main disadvantage of this type of sample is that it can detect failures in adherence to the treatment only when the analysis is performed shortly after the missed event (6).…”
Section: Discussionmentioning
confidence: 99%
“…Since 6-MP is widely used in chemotherapy, it is important to develop and validate analytical methods for its determination in pharmaceutical dosage forms. Review of literature has revealed that all methods reported for the estimation of 6-MP are useful in estimating 6-MP in biological samples (Sorouraddin et al, 2011;Hawwa et al, 2009;Umrethia et al, 2006;Oliveira et al, 2004;Su et al, 1999;Mawatari et al, 1998;Sahnoun et al, 1990;Erdmann, Chan, Canafax, 1988;Rudy et al, 1988;Migulla, Prumke, Huller, 1987). So far no systematic HPLC method has been reported for determination of 6-MP in pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 99%